Comparative Study of Patients' Satisfaction between National Health Insurance Scheme-Insured and Un-Insured Patients Attending a Northern Nigerian Tertiary Hospital - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Background:Periodic patients' satisfaction surveys provide feedback to hospital management and staff regarding the quality of services rendered.Objectives:This study assessed and compared clients' satisfaction between National Health Insurance Scheme (NHIS) insured and un-insured patients attending Aminu Kano Teaching Hospital.Materials and Methods:A cross-sectional design, using a mixed method of data collection was used to assess the levels of satisfaction of 149 NHIS-insured and 150 un-insured patients selected by systematic sampling. Using structured interviewer-administered questionnaires and focused group discussions (FGD), patient satisfaction was assessed and analysed using SPSS statistical software, with p-value set at 0.05.Results:The two study arms were not statistically different in all the socio-demographic characteristics assessed (P> 0.05). Eight aspects of care were significantly different between the two study groups at bi-variate level. However, on multivariable logistic regression, only two factors remained independent predictors of difference between the two groups: 'overall time spent in the hospital' (aOR; 95% CI: 0.41; 0.23, 0.69) and 'satisfaction with last visit out of pocket expenditure' (aOR; 95% CI: 0.40; 0.21, 0.83). 'Duration of NHIS registration', 'time taken to hospital' and 'last visit out of pocket expenditure' were found to be determinants of satisfaction. The FGDs revealed improvements in services upon getting insured, with the main areas of dissatisfaction being; waiting time, appointment intervals, missing laboratory results and costs.Conclusion:Patients generally expressed high levels of satisfaction with the different aspects of care provided in the hospital, with the insured patients having higher levels of satisfaction in nearly all domains. Improved NHIS coverage could markedly improve patients' access and satisfaction with services.